Consumo y salud - Sánchez-barbudo Ruiz-tapiador, Miguel-C (Aula, 2009)
RESUMEN: El tema «CONSUMO Y SALUD» está enfocado desde el punto de vista de la función importantísima del Profesor. Tiene como finalidad poner de manifiesto el marco dentro del cual el consumo es útil y beneficioso para la salud, tanto individual como colectiva. Al mismo tiempo, intenta orientar la acción educativa del Profesor para que, conjuntamente con su ejemplo, encauce el desarrollo de la personalidad del alumno y pueda éste integrarse en esta sociedad de consumo como ciudadano responsable, capaz de elegir libremente entre conductas positivas para la salud y rechace las conductas negativas. SUMMARY: The topic «CONSUMER SOCIETY AND HEALTH» is approached from the teacher’s point of view, whose function in introducing this subject to the students is most important. The purpose is to show the framework within which consuming is useful and advantageous for both an individual and collective health. At the same time, the article intends to give directions to the teacher’s educative task. The aim is for the teacher, helped by his exemplary behaviour, to guide students’ personality development and on that account to help them to join consumer society in a responsible way and to enable them to both choose freely among positive consumer attitudes to their health and reject the negative ones.